Using World Breastfeeding Week to Transform Institutional Culture. Issue 2 (March 2020) - Spatz, Diane L.
Abstract : Our breastfeeding expert, Dr. Spatz, provides details of her hospital's celebration for world breastfeeding week and encourages other hospitals to develop similar activities to promote human milk and breastfeeding.